2006
DOI: 10.1111/j.1471-4159.2006.03786.x
|View full text |Cite
|
Sign up to set email alerts
|

NAAG peptidase inhibitor increases dialysate NAAG and reduces glutamate, aspartate and GABA levels in the dorsal hippocampus following fluid percussion injury in the rat

Abstract: Traumatic brain injury (TBI) produces a rapid and excessive elevation in extracellular glutamate that induces excitotoxic brain cell death. The peptide neurotransmitter N-acetylaspartylglutamate (NAAG) is reported to suppress neurotransmitter release through selective activation of presynaptic group II metabotropic glutamate receptors. Therefore, strategies to elevate levels of NAAG following brain injury could reduce excessive glutamate release associated with TBI. We hypothesized that the NAAG peptidase inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
119
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(130 citation statements)
references
References 68 publications
(93 reference statements)
11
119
0
Order By: Relevance
“…Consistent with our behavioral data with ZJ43 and LY341495 and in the context of this model, a group II mGluR agonist reduces PCP-induced glutamate efflux as well as motor and cognitive behaviors (9). Similarly, we also found that ZJ43 induced elevation of synaptic NAAG levels reduces glutamate efflux (38).…”
Section: Models Of Naag and Schizophreniasupporting
confidence: 79%
See 3 more Smart Citations
“…Consistent with our behavioral data with ZJ43 and LY341495 and in the context of this model, a group II mGluR agonist reduces PCP-induced glutamate efflux as well as motor and cognitive behaviors (9). Similarly, we also found that ZJ43 induced elevation of synaptic NAAG levels reduces glutamate efflux (38).…”
Section: Models Of Naag and Schizophreniasupporting
confidence: 79%
“…Given the IC 50 and Ki of ZJ43 of 2.4 nM and 0.9 nM respectively when tested against human GCPII (37), these behaviorally effective doses of ZJ43 are clearly within the range required to substantially inhibit the activity of NAAG peptidases. Consistent with this conclusion, we have demonstrated that this dose range of ZJ43 significantly elevates extracellular NAAG levels and decreases glutamate release in the rat hippocampus following traumatic brain injury (38). While we do not yet know the full time course of inhibition of NAAG peptidases that is achieved by a single i.p.…”
Section: Efficacy Of Naag Peptidase Inhibitionsupporting
confidence: 70%
See 2 more Smart Citations
“…Microdialysis was initiated 10 min prior to injury and treatment, resulting in one sample before stretch injury and two samples collected at 10 and 20 min after stretch injury. Dialysates were then frozen, and glutamate levels were later analyzed by HPLC as described previously (Zhong et al, 2006).…”
Section: Fig 1 Microdialysis Sampling Apparatus Flexcellmentioning
confidence: 99%